Method for constructing Ni / SnS2@Ni(OH)2 using carbon cloth template
By constructing Ni/SnS2@Ni(OH)2 on a carbon cloth template, the preparation method for in-situ growth of Ni(OH)2 nanosheet double-array structural materials of Ni mixed SnS2 arrays in the prior art is solved. Problem, a supercapacitor positive electrode material with high specific surface area and high conductivity has achieved the effect of high power density and area specific capacity.
Patent Information
- Application Number
- CN202210242821.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-03-11
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2042-03-11
AI Technical Summary
In the prior art, there are fewer preparation methods for in-situ growth of Ni(OH)2 nanosheet double-array structure materials for Ni-parameter SnS2 arrays for supercapacitor positive electrode materials, and the specific surface area and conductivity of the material are not sufficiently improved. .
The method of constructing Ni/SnS2@Ni(OH)2 through a carbon cloth template includes preparing a Ni-doped SnS2 nanosheet array and growing ultra-thin Ni(OH)2 nanosheets in situ on the SnS2 nanosheet array. Improve the specific surface area and conductivity of the material.
The supercapacitor positive electrode material with high specific surface area and high conductivity has high power density and area specific capacity, and is suitable for high power, high safety and power fields.
Smart Images

Figure CN114613607B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of supercapacitor positive electrode material synthesis, and specifically relates to a carbon cloth template to construct Ni / SnS 2 @Ni(OH) 2 method. Background Art
[0002] With the excessive exploitation and rapid consumption of fossil energy, energy problems and environmental degradation have attracted much attention. At present, the development of clean, low-cost and environmentally friendly energy storage components to alleviate the current energy crisis in society is of great significance for the development of the national economy and the realization of sustainable development. At present, supercapacitors are considered to be one of the effective ways as emerging energy storage components. Studies have shown that: ① Compared with lithium-ion batteries, supercapacitor materials have higher power density and can achieve rapid charging and discharging; ② Aqueous supercapacitor materials are green, pollution-free and environmentally friendly, and have application value in the field of power energy.
[0003] There are literature reports on the preparation of in-situ Sn sulfide loaded on carbon cloth for supercapacitor positive electrode materials, but the preparation of Ni-doped SnS 2 In-situ growth of Ni(OH) 2 There are few reports on the use of nanosheet double array structure materials in supercapacitor systems. 2 Nanosheet arrays and SnS 2 In situ growth of ultrathin Ni(OH) on nanosheet arrays 2 Nanosheets greatly improve SnS 2 The specific surface area of the nanosheet array increases the specific capacitance. 2 In-situ growth of Ni(OH) 2 Nanosheet double array structure materials have rarely been reported as positive electrode materials for supercapacitors. Summary of the invention
[0004] The purpose of the present invention is to provide a carbon cloth template to construct Ni / SnS 2 @Ni(OH) 2 The cathode material is green, environmentally friendly, and has a high specific surface area and high conductivity. Compared with other cathode materials grown in situ, it has a high power density and area specific capacity. This indicates that it has great application potential in the fields of high power, high safety and power use.
[0005] The technical solution adopted by the present invention is to construct Ni / SnS 2 @Ni(OH) 2 The method is implemented according to the following steps:
[0006] Step 1, preparation of Ni-doped SnS 2 Nanosheet arrays;
[0007] Step 2, preparation of Ni / SnS 2 @Ni(OH) 2 .
[0008] The present invention is also characterized in that:
[0009] Step 1 is as follows:
[0010] Step 1.1, the chemicals used include nitric acid HNO 3 , sulfuric acid H 2 SO 4 , Tin tetrachloride SnCl 4 、Nickel chloride hexahydrate NiCl 2 6H 2 O and thioacetamide TAA. Before synthesis, the carbon cloth was immersed in HNO 3 and H 2 SO 4 In the mixed solution, surface impurities were removed and activated, and then dried in air, which was recorded as sample A;
[0011] Step 1.2: Prepare anhydrous SnCl 4 、NiCl 2 6H 2 O and thioacetamide TAA were dissolved in deionized water and stirred, which was recorded as solution B;
[0012] Step 1.3, transfer sample A and solution B to a polytetrafluoroethylene-lined autoclave at the same time, keep for a period of time, and then cool naturally to room temperature to obtain the Ni / SnS in situ grown on the carbon cloth surface. 2 The precursor was ultrasonically washed several times with deionized water and ethanol and then dried overnight in vacuum to obtain Ni-doped SnS 2 Nanosheet array; denoted as sample C;
[0013] The size of the carbon cloth in step 1.1 is 1×3~2×3cm, and the HNO 3 and H 2 SO 4 The mass ratio of the mixed solution is 3:1;
[0014] In step 1.2, anhydrous SnCl 4 1~3mmol, NiCl 2 6H 2 O is 0.1-0.3 mmol, thioacetamide TAA is 0.8-1 mmol, deionized water is 5-30 mL, stirring is magnetic stirring, and the stirring time is 20-30 min;
[0015] Wherein in step 1.2, the molar ratio of anhydrous tin chloride, nickel chloride hexahydrate and thioacetamide is 10:1.5:5 to 10:0.5:5;
[0016] Wherein the holding time in step 1.3 is 4 to 8 hours, the holding temperature is 150 to 170°C, and the vacuum drying temperature is 60 to 90°C;
[0017] Step 2 is as follows:
[0018] Step 2.1, 0.1-1.5 mmol NiCl 2 6H 2 O and 0.1-5 mmol urea were dissolved in 5-30 ml deionized water and stirred magnetically at room temperature until a light green transparent solution was formed, which was recorded as solution D;
[0019] Step 2.2, the sample C obtained in step 1 and the solution D obtained in step 2.1 are simultaneously transferred to an autoclave and kept for a period of time. After naturally cooling to room temperature, the obtained sample is rinsed with ethanol and ultrapure water for several times, and then vacuum dried overnight to obtain Ni / SnS 2 @Ni(OH) 2 Sample, denoted as sample E;
[0020] In step 2.1, NiCl 2 6H 2 O is 0.1-1.5mmol, urea is 0.1-5mmol, and deionized water is 5-30ml;
[0021] Wherein in step 2.1, the molar ratio of nickel chloride to urea is 1:2 to 1:4;
[0022] The holding time in step 2.2 is 1 to 2 hours, the holding temperature is 90 to 110° C., and the vacuum drying temperature is 60 to 90° C.
[0023] The beneficial effects of the present invention are:
[0024] The carbon cloth template of the present invention constructs Ni / SnS 2 @Ni(OH) 2 The method is simple and low in cost. The prepared supercapacitor cathode material has high area specific capacity and power density, and exhibits good electrochemical performance. 2 @Ni(OH) 2 The material is innovative and has good electrochemical properties and is practical. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1The carbon cloth template of the present invention is used to construct Ni / SnS 2 @Ni(OH) 2 The method of Ni(OH) 2 Successfully loaded on Ni / SnS2 surface;
[0026] Figure 2 The carbon cloth template of the present invention constructs Ni / SnS 2 @Ni(OH) 2 Ni / SnS prepared by 2 @Ni(OH) 2 Material morphology diagram;
[0027] Figure 3 The carbon cloth template of the present invention is used to construct Ni / SnS 2 @Ni(OH) 2 Ni / SnS prepared by 2 @Ni(OH) 2 Constant current charge-discharge curves of the material in 2M KOH electrode solution. DETAILED DESCRIPTION
[0028] The present invention is described in detail below with reference to the accompanying drawings and specific embodiments.
[0029] The present invention provides a carbon cloth template for constructing Ni / SnS 2 @Ni(OH) 2 The method is implemented according to the following steps:
[0030] Step 1, preparation of Ni-doped SnS 2 Nanosheet arrays:
[0031] Step 1.1, the chemicals used include nitric acid HNO 3 , sulfuric acid H 2 SO 4 , Tin tetrachloride SnCl 4 、Nickel chloride hexahydrate NiCl 2 6H 2 O and thioacetamide TAA. Before synthesis, the carbon cloth was immersed in HNO 3 and H 2 SO 4 The mixed solution was used to remove surface impurities and activation, and then dried in air, which was recorded as sample A. The size of the carbon cloth was 1×3 to 2×3 cm, and HNO 3 and H 2 SO 4 The mass ratio of the mixed solution is 3:1;
[0032] Step 1.2: Prepare anhydrous SnCl 4 、NiCl 2 6H2 O and thioacetamide TAA were dissolved in deionized water and stirred, which was recorded as solution B. Anhydrous SnCl 4 1~3mmol, NiCl 2 6H 2 O is 0.1-0.3 mmol, thioacetamide TAA is 0.8-1 mmol, deionized water is 5-30 mL, stirring is magnetic stirring, and the stirring time is 20-30 min; the anhydrous SnCl 4 、NiCl 2 6H 2 The molar ratio of O and thioacetamide TAA is 10:1.5:5 to 10:0.5:5;
[0033] Step 1.3, transfer sample A and solution B to a polytetrafluoroethylene-lined autoclave at the same time, keep the temperature at 150-170°C for 4-8 hours, and then cool naturally to room temperature to obtain the in-situ grown Ni / SnS on the carbon cloth surface. 2 The precursor was ultrasonically washed several times with deionized water and ethanol, and then dried overnight in a vacuum at a temperature of 60-90 °C to obtain Ni-doped SnS 2 Nanosheet array; denoted as sample C;
[0034] Step 2, preparation of Ni / SnS 2 @Ni(OH) 2 :
[0035] Step 2.1, 0.1-1.5 mmol NiCl 2 6H 2 O and 0.1-5 mmol urea are dissolved in 5-30 ml deionized water, with the molar ratio of nickel chloride to urea being 1:2-1:4, and magnetic stirring is performed at room temperature until a light green transparent solution is formed, which is recorded as solution D, NiCl 2 6H 2 O is 0.1-1.5mmol, urea is 0.1-5mmol, and deionized water is 5-30ml;
[0036] Step 2.2, the sample C obtained in step 1 and the solution D obtained in step 2.1 are simultaneously transferred to an autoclave for 1 to 2 hours at a temperature of 90 to 110°C. After naturally cooling to room temperature, the obtained sample is rinsed with ethanol and ultrapure water several times, and then vacuum dried overnight at a vacuum drying temperature of 60 to 90°C to obtain Ni / SnS 2 @Ni(OH) 2 The sample is recorded as sample E.
[0037] like Figure 1As shown in the figure, (001), (100), (101) correspond to SnS in the PDF card. 2 phase, and the peaks are offset compared with the standard card. (003) and (110) correspond to Ni(OH) in the PDF card. 2 phase; it can be seen that Ni is successfully doped in SnS 2 In the system, Ni(OH) 2 Successfully loaded on Ni / SnS 2 surface;
[0038] like Figure 2 As shown, Ni / SnS 2 @Ni(OH) 2 The material maintains the morphology of nanosheet arrays, and the sheet thickness is about 15nm;
[0039] like Figure 3 As shown, I, II, III, IV, and V represent current densities of 5, 10, 20, 30, and 40 mA cm -2 The constant current charge and discharge spectrum corresponding to the conditions; Ni / SnS 2 @Ni(OH) 2 -CC electrode at current densities of 5 (I), 10 (II), 20 (III), 30 (IV) and 40 (V) mA cm -2 The specific capacitances are 4.78, 4.16, 3.57, 3.17 and 2.86 Fcm respectively. -2 (corresponding to 1991, 1662, 1428, 1266, 1144Fg respectively -1 );
[0040] Embodiment 1:
[0041] 1) Preparation of Ni-doped SnS 2 Nanosheet arrays:
[0042] All chemicals (analytical grade) were used as received without further treatment; prior to synthesis, carbon cloth (1 × 3 cm) was immersed in HNO with a mass ratio of 3:1 3 and H 2 SO 4 The mixed solution was cleaned of surface impurities and activated, and then dried in air, which was recorded as sample A. 1 mmol of anhydrous SnCl 4 、0.1mmolNiCl 2 6H 2O and 0.8mmol thioacetamide (TAA) were dissolved in 25mL deionized water and magnetically stirred for 20min, which was recorded as solution B. Sample A and solution B were simultaneously transferred to a 10-50mL polytetrafluoroethylene-lined autoclave, maintained at 150-170℃ for 4-8h, and then naturally cooled to room temperature. The Ni / SnS on the obtained carbon cloth 2 The precursor was ultrasonically washed several times with ultrapure water and ethanol and then dried overnight under vacuum at 60 °C, which was recorded as sample C;
[0043] 2) Preparation of Ni / SnS 2 @Ni(OH) 2
[0044] 0.1~1.5mmolNiCl 2 6H 2 O and 0.1-5 mmol urea were dissolved in 5-30 ml ultrapure water and magnetically stirred at room temperature until a light green transparent solution was formed, which was recorded as solution D. Then, sample C and solution D were simultaneously transferred to a 10-50 ml autoclave and kept at 90-110°C for 1-2 h. After naturally cooling to room temperature, the obtained sample was rinsed with ethanol and ultrapure water several times, and then vacuum dried at 60°C overnight, which was recorded as sample E.
[0045] Embodiment 2:
[0046] 1) Preparation of Ni-doped SnS 2 Nanosheet arrays:
[0047] All chemicals (analytical grade) were used as received without further treatment; prior to synthesis, carbon cloth (1 × 3 cm) was immersed in HNO with a mass ratio of 3:1 3 and H 2 SO 4 The mixed solution was cleaned of surface impurities and activated, and then dried in air, which was recorded as sample A. 2 mmol, anhydrous SnCl 4 , 0.2 mmol NiCl 2 6H 2 O and 0.9mmol thioacetamide (TAA) were dissolved in 5-30mL deionized water and magnetically stirred for 20min, which was recorded as solution B. Sample A and solution B were simultaneously transferred to a 10-50ml polytetrafluoroethylene-lined autoclave, kept at 160℃ for 6h, and then naturally cooled to room temperature. The Ni / SnS on the obtained carbon cloth 2 The precursor was ultrasonically washed several times with ultrapure water and ethanol and then dried overnight under vacuum at 60 °C, which was recorded as sample C;
[0048] 2) Preparation of Ni / SnS 2 @Ni(OH) 2
[0049] 0.1~1.5mmolNiCl 2 6H 2 O and 0.1-5 mmol urea were dissolved in 5-30 ml ultrapure water and magnetically stirred at room temperature until a light green transparent solution was formed, which was recorded as solution D. Then, sample C and solution D were simultaneously transferred to a 10-50 ml autoclave and kept at 90-110°C for 1-2 h. After naturally cooling to room temperature, the obtained sample was rinsed with ethanol and ultrapure water several times, and then vacuum dried at 60°C overnight, which was recorded as sample E.
[0050] Embodiment 3:
[0051] 1) Preparation of Ni-doped SnS 2 Nanosheet arrays:
[0052] All chemicals (analytical grade) were used as received without further treatment; prior to synthesis, carbon cloth (1 × 3 cm) was immersed in HNO with a mass ratio of 3:1 3 and H 2 SO 4 The mixed solution was cleaned of surface impurities and activated, and then dried in air, which was recorded as sample A. 2 mmol anhydrous SnCl 4 、0.2mmolNiCl 2 6H 2 O and 0.9mmol thioacetamide (TAA) were dissolved in 5-30mL deionized water and magnetically stirred for 20min, which was recorded as solution B. Sample A and solution B were simultaneously transferred to a 10-50ml polytetrafluoroethylene-lined autoclave, kept at 170℃ for 4h, and then naturally cooled to room temperature. The Ni / SnS on the obtained carbon cloth 2 The precursor was ultrasonically washed several times with ultrapure water and ethanol and then dried overnight under vacuum at 60 °C, which was recorded as sample C;
[0053] 2) Preparation of Ni / SnS 2 @Ni(OH) 2
[0054] 0.1~1.5mmolNiCl 2 6H 2 O and 0.1-5 mmol urea were dissolved in 5-30 mmol ultrapure water and magnetically stirred at room temperature until a light green transparent solution was formed, which was recorded as solution D. Then, sample C and solution D were simultaneously transferred to a 10-50 mmol autoclave and kept at 90-110°C for 1-2 h. After naturally cooling to room temperature, the obtained sample was rinsed with ethanol and ultrapure water several times, and then vacuum dried at 60°C overnight, which was recorded as sample E.
[0055] Embodiment 4:
[0056] 1) Preparation of NiCo 2 S 4 Nanotube arrays:
[0057] 1) Preparation of Ni-doped SnS 2 Nanosheet arrays:
[0058] All chemicals (analytical grade) were used as received without further treatment. Before synthesis, carbon cloth (1 × 3 cm) was immersed in HNO 3 and H 2 SO 4 The mixed solution was treated with 1-3 mmol anhydrous SnCl 4 、0.1~0.3mmolNiCl 2 6H 2 O and 0.8-1 mmol thioacetamide (TAA) were dissolved in 5-30 mL deionized water and magnetically stirred for 20 min, which was recorded as solution B. Sample A and solution B were simultaneously transferred to a 10-50 ml polytetrafluoroethylene-lined autoclave, kept at 150-170 ° C for 4-8 h, and then naturally cooled to room temperature. The Ni / SnS on the obtained carbon cloth 2 The precursor was ultrasonically washed several times with ultrapure water and ethanol and then dried overnight under vacuum at 60 °C, which was recorded as sample C;
[0059] 2) Preparation of Ni / SnS 2 @Ni(OH) 2
[0060] 1mmolNiCl 2 6H 2 O and 3 mmol urea were dissolved in 5-30 ml ultrapure water and magnetically stirred at room temperature until a light green transparent solution was formed, which was recorded as solution D. Then sample C and solution D were simultaneously transferred to a 10-50 ml autoclave and kept at 100 °C for 1 h. After naturally cooling to room temperature, the obtained sample was rinsed with ethanol and ultrapure water several times and then vacuum dried at 60 °C overnight, which was recorded as sample E.
Claims
1. A method for constructing Ni / SnS2@Ni(OH)2 using a carbon cloth template, characterized in that: Follow the steps below to implement it: Step 1, preparing Ni-doped SnS2 nanosheet arrays; The step 1 is specifically as follows: Step 1.1, the chemicals used include nitric acid HNO3, sulfuric acid H2SO4, tin tetrachloride SnCl4, nickel chloride hexahydrate NiCl2·6H2O and thioacetamide TAA. Before synthesis, the carbon cloth is immersed in a mixed solution of HNO3 and H2SO4 to remove surface impurities and activate, and then dried in air, which is recorded as sample A; in step 1.1, the size of the carbon cloth is 1×3 to 2×3 cm, and the mass ratio of the mixed solution of HNO3 and H2SO4 is 3:1; Step 1.2, dissolving anhydrous SnCl4, NiCl2·6H2O and thioacetamide TAA in deionized water and stirring, recorded as solution B; in step 1.2, anhydrous SnCl4 is 1-3 mmol, NiCl2·6H2O is 0.1-0.3 mmol, thioacetamide TAA is 0.8-1 mmol, deionized water is 5-30 mL, stirring is magnetic stirring, and the stirring time is 20-30 min; in step 1.2, the molar ratio of the anhydrous SnCl4, NiCl2·6H2O and thioacetamide TAA is 10:1.5:5-10:0.5:5; Step 1.3, transfer sample A and solution B to a polytetrafluoroethylene-lined autoclave at the same time, keep for a period of time, and then cool naturally to room temperature, wash the Ni / SnS2 precursor grown in situ on the carbon cloth surface with deionized water and ethanol ultrasonically for several times, and then dry it in vacuum overnight to obtain a Ni-doped SnS2 nanosheet array; recorded as sample C; in step 1.3, the holding time is 4 to 8 hours, the holding temperature is 150 to 170°C, and the vacuum drying temperature is 60 to 90°C; Step 2, preparing Ni / SnS2@Ni(OH)2; The step 2 is specifically as follows: Step 2.1, dissolve 0.1-1.5 mmol NiCl2·6H2O and 0.1-5 mmol urea in 5-30 ml deionized water, and stir magnetically at room temperature until a light green transparent solution is formed, which is recorded as solution D; In step 2.1, NiCl26H2O is 0.1-1.5 mmol, urea is 0.1-5 mmol, deionized water is 5-30 ml, and the molar ratio of nickel chloride to urea is 1:2-1:4; Step 2.2, transfer the sample C obtained in step 1 and the solution D obtained in step 2.1 to an autoclave at the same time and keep them for a period of time. After naturally cooling to room temperature, the obtained samples are rinsed with ethanol and ultrapure water several times, and then vacuum dried overnight to obtain a Ni / SnS2@Ni(OH)2 sample, recorded as sample E. The holding time in step 2.2 is 1 to 2 hours, and the holding temperature is 90 to 110°C; the vacuum drying temperature is 60 to 90°C.